2018
DOI: 10.1051/e3sconf/20183502002
|View full text |Cite
|
Sign up to set email alerts
|

Tectono-thermal Evolution of the Lower Paleozoic Petroleum Source Rocks in the Southern Lublin Trough: Implications for Shale Gas Exploration from Maturity Modelling

Abstract: The Lower Paleozoic basins of eastern Poland have recently been the focus of intensive exploration for shale gas. In the Lublin Basin potential unconventional play is related to Lower Silurian source rocks. In order to assess petroleum charge history of these shale gas reservoirs, 1-D maturity modeling has been performed. In the Łopiennik IG-1 well, which is the only well that penetrated Lower Paleozoic strata in the study area, the uniform vitrinite reflectance values within the Paleozoic section are interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…11c). Both estimates are similar to that from maturity modelling based on the VR and porosity data (Botor, 2018;Botor et al, 2019a…”
Section: łOpiennik Ig-1 330supporting
confidence: 72%
See 1 more Smart Citation
“…11c). Both estimates are similar to that from maturity modelling based on the VR and porosity data (Botor, 2018;Botor et al, 2019a…”
Section: łOpiennik Ig-1 330supporting
confidence: 72%
“…Maturity modelling, based on downhole VR profiles (Fig. 5), showed that the thermal evolution in the Lublin Basin was related to burial in Devonian-Carboniferous times with the most prominent temperature increase in the late Carboniferous (Botor et al, 2002;Karnkowski, 2003;Kosakowski et al, 2013;Botor, 2018;Botor et al, 2019a,b). A fluid flow influence on thermal maturity in this area was suggested by Poprawa andŻywiecki (2005) based on combined analysis of fluid inclusions and modelling of organic maturation.…”
Section: Previous Thermal History Studiesmentioning
confidence: 99%
“…The locations of PolandSPAN™ seismic profiles (PL1-5100, 5300, 5400) used in Fig. 2 al., 2018;Mazur et al, 2018b). The initially uniform early Paleozoic basin was subsequently separated by differential exhumation in three distinct parts: the Baltic, Podlasie, and Lublin basins, straddling the SW slope of the EEP from the NW to SE (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Permian and Mesozoic rocks in the Baltic Basin show much lower thermal maturity compared to the lower Paleozoic sediments, usually below 0.6 % VR (Grotek, 1999(Grotek, , 2006Poprawa et al, 2010). Further SE, thermal maturity is variable in the Carboniferous and Devonian-Carboniferous strata of the Podlasie and Lublin basins, respectively (Poprawa and Pacześnia, 2002;Grotek, 2005;Botor et al, 2002Botor et al, , 2019a. However, the Permian-Mesozoic sediments consistently show low thermal maturity below 0.5 % VR in these basins (Grotek, 2005(Grotek, , 2006(Grotek, , 2016.…”
Section: Previous Thermal History Studiesmentioning
confidence: 99%
See 1 more Smart Citation